THE EMISSIONS EMITTED BY SPRUCE THERMOWOOD WITH AND WITHOUT SURFACE FINISHED (Innovation in Woodworking Industry and Engineering design, 2026)
This paper investigates the problematic of VOC emissions emitted by the massive spruce wood and by heat treated wood at temperatures 180 °C and 200 °. In this contribution is investigated the influence on the temperature of the spruce wood heat treatment on the quality and quantity content of volatile organic compounds, especially on the amount of emitted Phenol and Furfural. This contribution researches the correlation between the times after the modification of heat-treated wood and amount and contents of VOC emitted by this heat treated spruce wood. This study contains the results of the influence of finished Spruce heat-treated wood by the water born lacquer on emissions of VOC.